Sleep regularity in athletes: Comparing sex, competitive level and sport type - Alves Facundo, L.; Martins Brant, V.; Carvalho Guerreiro, R.; de Araújo Andrade, H.; Mazzilli Louzada, F.; Silva, A.; Túlio de Mello, M. (Chronobiology International, 2022)
This study aims to describe the athletes` sleep regularity using the Sleep Regularity Index (SRI) and determine whether factors, such as sex, competitive level and sport type, could affect the sleep/wake rhythm. It is a descriptive, cross-sectional study consisting of 172 athletes (25 ± 7 y old; 45 women). Seventy-three competed in team sports and 99 in individual sports. Furthermore, 56 competed in the international level, 95 in the national and 21 in the regional. We recorded the SRI values for at least 5 d via continuous actigraphy. We recorded a mean SRI value of 73 ± 12. We found no significant differences between athletes` sleep parameters in relation to sleep regularity. Furthermore, SRI data showed no correlations (Spearman`s p) with sleep parameters, bed time and wake time. Female athletes (p = 0.001) and individual sport athletes (p = 0.001) reported better sleep regularity than their counterparts. International-level athletes reported better sleep regularity than those in other competitive levels (national: p = 0.001; regional: p = 0.024). Our study showed that international level athletes, female athletes and individual sport athletes reported better sleep regularity. Additionally, SRI data showed no correlation with athletes` sleep parameters, bed and wake time.